Effects of relative humidity and particle type on the performance and service life of automobile cabin air filters. Issue 6 (2nd June 2016) - He, Xu; Brem, Benjamin T.; Bahk, Yeon Kyoung; Kuo, Yu-Ying; Wang, Jing
ABSTRACT: Cabin air filters are the main barrier for protecting automobile passengers from on road particulate matter. There are many studies about the evaluation of their performance in terms of filtration efficiency. However, the knowledge about the loading capacity of them is still lacking. Meanwhile, there has been no quantitative method to estimate the proper filter service life time. This study focuses on testing the loading capacity of different types of cabin air filters under the conditions of different relative humidity values and particle types. The results indicate that when the relative humidity increases, the activated carbon coated filters can adsorb significant amounts of water with no significant increase of the pressure drop. The normal fibrous filters show in contrast negligible water adsorbance. Compared with the filters loaded by Arizona road dust only, loading the filters by Arizona road dust and soot particles simultaneously will result in the steeper loading curves as well as the shift of most penetrating particle size to the smaller diameter. Finally, a new method to estimate the proper service life time of the cabin air filters is suggested based on the loading curves. Copyright © 2016 American Association for Aerosol Research